Keputusan Pendanaan Dan Kebijakan Dividen Perusahaan Pada Tahap Growth Dan Mature - Faznil Husna S. Rasyad; Suad Husnan (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2019)
This study empirically examines the Pecking Order Theory and Dividend Residual Theory in growth and mature firms, whether the growth firms tend to be stronger following the Pecking Order Theory and Dividend Residual Theory than mature firms. In addition, this study also examine whether the proportion of long-term debt and the proportion of retained earnings growth firms higher than mature firms. The sample used is non-financial companies listed on the Indonesia Stock Exchange 2010-2013. Hypothesis testing using simple regression analysis and Independent Sample T-Test. The results showed that both groups of growth and mature firms not follow Pecking Order Theory in the capital structure decision, but for testing Dividend Residual Theory indicate that the growth firms tend to be stronger following the Dividend Residual Theory in dividend policy, while mature firms do not follow the Dividend Residual Theory in policy dividend. Independent Sample T-Test results showed that the proportion of long-term debt and the proportion of retained earnings growth firms higher than mature firms.